Labour market and structural adjustment in Latin America: an appraisal of the social effects in the 1980s: background paper - Infante, Ricardo (I.L.O. PREALC Port of SpainTT, 1991)
Describes the economic situation in the industrialized economies and the effects which it excited on the labour market which resulted in a greater flexibility in employment, hiring of labour and the wage system. Examines the adjustment policies adopted by regional governments focussing on Chile, Costa Rica and Mexico.